SESI ORGANOLEPTIK PRODUK CEMILAN UMKM KINAMANG; SEDIAAN INFORMASI PRODUKSI UMKM LINGKAR KAMPUS BONE BOLANGO - Tahir, Muh; Ilham, Fahrul (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2023)
As a business actor in the food sector, Kinamang MSMEs have the potential to develop around college campuses. Various snack products are produced with neat packaging and meet the requirements for self-service display cases. Among the snack products are corn sticks (bindhe) with original flavor variants, skipjack fish flavor, nike fish flavor and sagela fish flavor. In the community service session, an organoleptic test was carried out to provide scientific information regarding useful product variations in the production process. Is there an influence of these three variants on the level of consumer preference represented by the panelists? Organoleptic tests on the original corn stick snack and its three variants showed that adding the fish flavor variant had no real effect on the taste of the corn stick (bindhe). The organoleptic test with a completely random pattern at a 95% confidence level obtained an F-count F-table value so that the flavor variants did not affect consumer preferences.